Gambaran Hasil Belajar Pelatihan Keterampilan Menyulam di PKBM Surya Padang - Silviana, Silviana; Syuraini, Syuraini (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was motivated by the low entrepreneurial skills of embroidering skills training participants at PKBM Surya Padang. One of the reasons for this low entrepreneurial ability is low learning outcomes. This study aims to obtain information about the learning outcomes of embroidering skills training participants after participating in the process of embroidering skills training at PKBM Surya Padang. This research includes quantitative descriptive research. The population of this study was training participants who took embroidering skills training at PKBM Surya Padang in 2018, totaling 20 people, all populations were taken as samples. The sampling technique used in this study is the census method. Techniques for collecting data using documents. The results of this study indicate that the learning outcomes of embroidering skills training participants are still relatively low.